2021
DOI: 10.1007/s10926-020-09944-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Attention and Working Memory Predict the Number of Days on Health-Related Benefits in the Year Following Occupational Rehabilitation

Abstract: Purpose The objective of this study was to investigate the association between cognitive and emotional functioning and the number of days on health-related benefits such as sick leave, work assessment allowance and disability pension. We investigated whether cognitive and emotional functioning at the start of rehabilitation and the change from the start to the end of rehabilitation predicted the number of days on health-related benefits in the year after occupational rehabilitation. Methods A sample of 317 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…The significant results regarding cognitive predictors of rehabilitation success suggest that even with individual vocational and psychosocial services, higher baseline cognitive functioning predicts better work-related outcomes. This is in line with studies showing that improvement in cognitive functioning can contribute to more positive outcomes of rehabilitation interventions ( 70 , 71 ). Furthermore, cognitive remediation has the potential to improve work outcomes of rehabilitation interventions ( 38 ).…”
Section: Discussionsupporting
confidence: 91%
“…The significant results regarding cognitive predictors of rehabilitation success suggest that even with individual vocational and psychosocial services, higher baseline cognitive functioning predicts better work-related outcomes. This is in line with studies showing that improvement in cognitive functioning can contribute to more positive outcomes of rehabilitation interventions ( 70 , 71 ). Furthermore, cognitive remediation has the potential to improve work outcomes of rehabilitation interventions ( 38 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although our results are novel for the normally working population they are in line with several studies on patients. For example, it has been shown that EF may predict absence from work following in-patient occupational rehabilitation ( Johansen et al, 2021 ) as well as for individuals with ADHD ( Biederman et al, 2006 ; Halleland et al, 2019 ). Another study compared remitted bipolar patients that were able to continue to be active (studying or working) with those who were inactive (e.g., unemployed, received early retirement benefit or being on long term sick leave; Drakopoulos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rehabilitation sample was divided into three sick leave groups based on how much each individual was on sick leave in the year after rehabilitation: 100-75%, 74-40% and 39-0%. The individuals belonging to these categories and a control group were compared in order to investigate whether there were differences in improvements in sustained attention and working memory both during and after rehabilitation, thus extending previous findings [9,10,16]. It was hypothesised that the degree of work participation is relevant to recovery of cognitive functioning in sick-listed individuals after occupational rehabilitation, where higher work participation would result in larger improvement in sustained attention and working memory.…”
Section: Introductionmentioning
confidence: 92%
“…The focus of this study is to explore the degree to which the amount of time spent at work positively influences memory and attention. These two domains were selected because it has been shown that attention and memory functions improve more than executive function and emotion regulation in occupational rehabilitation patients [9,10] as well as being associated with RTW [16]. Sustained attention and working memory were specifically selected as the cognitive constructs in the current study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation